When Developers Disagree: Divergent Advice as a Potential Catalyst for Protégé Growth - Feldman, Elana; Kahn, William (Organization Science, 2019)
Developmental relationships offer rich opportunities for personal growth, which enables people to operate effectively in complex work environments. Although it is now widely recognized that protégés typically have more than one developmental relationship simultaneously, few researchers have considered the ways in which developmental networks—comprising a protégé’s multiple developers—foster growth. We therefore know little about how protégés grow through their engagement in several concurrent relationships. In this paper, we suggest that understanding growth in the context of developmental networks requires viewing such networks as intertwined assemblages of dyadic relationships. Adopting this perspective, we theorize one way in which the interactions that protégés have across their various relationships may—cumulatively—catalyze growth. In our theorizing, we focus on a specific type of situation: instances when developers offer divergent advice about work-related issues. Our model traces how protégés cope with divergent advice through either an engaged grappling process or an avoidant retreating process. We theorize that whereas grappling activities yield high levels of growth, retreating activities produce no growth. However, we also suggest that protégés may oscillate back and forth between the grappling and retreating processes over time, thereby resulting in varying rather than binary growth outcomes. Our paper contributes to scholarship on developmental relationships and networks while also laying the groundwork for future empirical research.